1997
DOI: 10.1159/000310887
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Infections of the Eye in Immunocompromised Patients

Abstract: All opportunistic infections of the eye have their origin in the suppression of the immune system of the host. The immunosuppression can be acquired through the human immune deficiency virus or as a result of immunosuppressive therapy in solid-organ transplant recipients with a maintenance therapy of cyclosporin and prednisone or during chemotherapy in patients with myelo-proliferative disorders. Generally, in less than 2% could severe opportunistic infections of the eye, like cytomegalovirus (CMV) or herpes v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Cytomegalovirus (CMV) retinitis (CMVR) is very rare in transplanted patients. In solid organ transplant patients less than 2% develop CMVR (1, 2) even though the pediatric population is at higher risk, especially after primary CMV infection post transplant, where an incidence as high as 14% has been reported (3). After hematopoietic stem cell transplantation (SCT), the only larger study published on development of CMVR showed an incidence of 1.4% in patients who were alive after day 100 post transplant and who had developed a chronic clinical extensive graft‐versus‐host disease (GVHD) (4).…”
mentioning
confidence: 99%
“…Cytomegalovirus (CMV) retinitis (CMVR) is very rare in transplanted patients. In solid organ transplant patients less than 2% develop CMVR (1, 2) even though the pediatric population is at higher risk, especially after primary CMV infection post transplant, where an incidence as high as 14% has been reported (3). After hematopoietic stem cell transplantation (SCT), the only larger study published on development of CMVR showed an incidence of 1.4% in patients who were alive after day 100 post transplant and who had developed a chronic clinical extensive graft‐versus‐host disease (GVHD) (4).…”
mentioning
confidence: 99%
“…In a study by Crippa et al, 8 CMV retinitis was found to be a late complication of HSCT and was mainly seen in patients with antecedent CMV reactivation or disease. The median time of diagnosis of CMV retinitis was 251 days (range, 106–356 days).…”
Section: Discussionmentioning
confidence: 99%
“…CMV retinitis was the AIDS-defining diagnosis in about 5% of patients with HIV infections 7. Among SOT patients, <2% develop CMV retinitis; however, the pediatric population is at a higher risk 8. After HSCT, the only large study published on CMV retinitis development showed an incidence of 1.4% in patients who were alive 100 days post-transplant 9…”
Section: Introductionmentioning
confidence: 99%
“… reported the prevalence of ocular opportunistic infection, such as retinitis, in 0.69% kidney transplant recipients. Guembel and Ohrloff described severe CMV and HSV infections of the eye in < 2% of transplant and cancer patients with chemotherapy, analyzed together. Eid et al.…”
Section: Discussionmentioning
confidence: 99%